Topics in Almost Automorphy - N'Guérékata, Gaston M.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Since the publication of our first book [80], there has been a real resiu-gence of interest in the study of almost automorphic functions and their applications ([16, 17, 28, 29, 30, 31, 32, 40, 41, 42, 46, 51, 58, 74, 75, 77, 78, 79]). New methods (method of invariant s- spaces, uniform spectrum), and new concepts (almost periodicity and almost automorphy in fuzzy settings) have been introduced in the literature. The range of applications include at present linear and nonlinear evolution equations, integro-differential and functional-differential equations, dynamical systems, etc...It has become imperative to take a bearing of the main steps of the the ory. That is the main purpose of this monograph. It is intended to inform the reader and pave the road to more research in the field. It is not a self contained book. In fact, [80] remains the basic reference and fimdamental source of information on these topics. Chapter 1 is an introductory one. However, it contains also some recent contributions to the theory of almost automorphic functions in abstract spaces. VIII Preface Chapter 2 is devoted to the existence of almost automorphic solutions to some Unear and nonUnear evolution equations. It con tains many new results. Chapter 3 introduces to almost periodicity in fuzzy settings with applications to differential equations in fuzzy settings. It is based on a work by B. Bede and S. G. Gal [40].
and Preliminaries -- Almost Automorphic Evolution Equations -- Almost Periodicity in Fuzzy Setting -- Almost Automorphy in Fuzzy Setting.
Keywords: Mathematical analysis; Analysis (Mathematics).; Functional analysis; Fourier analysis; Dynamics; Ergodic theory; Partial differential equations; Analysis; Functional Analysis; Fourier Analysis; Dynamical Systems and Ergodic Theory; Partial Differential Equations